A microbiological evaluation of the use of denture cleansers in combination with an oral rinse in complete denture patients - Srinivasan Murali; Gulabani Manish (Wolters Kluwer Medknow Publications, 2010)
Background and Aim : Patients with complete dentures more occasionally neglect their denture and oral health by improper maintenance of dentures, resulting in bad oral and denture hygiene. This may lead to a host of multiple local and systemic problems such as stomatitis, bacterial and fungal infections, reservoirs for distant infections, denture stains and bad breath. Most denture wearers maintain their dentures with simple manual cleansing methods, which are not adequate to effectively sanitize the reservoir of microorganisms inhabiting the denture surfaces. The aim of this study was to compare the efficacy of the use of a denture cleanser and compare it with an adjunct use of chlorhexidine mouth rinse along with the denture cleanser and possibly suggest it as a suitable protocol. Materials and Methods : Two groups of complete denture patients were selected for the study. The total number of patients in each group was 12 and the total period of the study was 21 days. Three sets of microbiological samples were collected from each patient: before the start of the study, on day 8 and on day 21 of the study. The first sample was collected after an initial washover period (7 days) with plain water before the start of the study and the second set after 1 week of study initiation, where group-1 followed protocol-I (denture cleanser only) and group-2 followed protocol-II (denture cleanser and mouth rinse). A second washout period of 7 days followed and a crossover of the protocol was performed for the groups and followed for 1 week. Then, a third set of samples were collected. The colony-forming units were calculated for each patient for each sample and statistically analyzed. Friedman test for non-parametric analysis was employed for the comparison within the groups and a Mann-Whitney test was used for the statistical comparison between the groups. Results : There was a definite reduction in the bacterial numbers and a significant statistical difference after administering the protocols in both the groups (P < 0.001). However, there was little significance on comparing the samples between the groups (P=0.026) in the initial study period, and there was no statistical significance when comparing the groups after the crossover (P=0.140). Conclusion : The use of denture cleansers definitely reduced the microbial numbers as compared to plain manual cleansing methods in complete dentures. Although there was a substantial decrease in the bacterial colonies after the use of the mouthwash, it was not statistically significant.